Transforming power sharing - Salloukh, Bassel F. (2017)
Lebanon’s corporate consociation is in institutional crisis. Given domestic constraints, however, a shift from corporate to liberal consociation is not an option. The alternative is to introduce institutional reforms that move power sharing in the direction of hybrid consociation. A substantial measure of state decentralization and PR voting in the context of a new MMP or PR electoral law are two such reforms that if applied synergistically may help stabilize the political system without changing the predetermined sectarian quota institutionalized in the Ta’if Accord or undermine the Muslim elite’s political economic prerogatives; increase the peacebuilding and statebuilding effectiveness of power sharing institutions; and incorporate into the political system excluded anti-sectarian groups. These changes may imbue the postwar political economic order with a measure of representation, accountability, and stability. A hybrid consociation arrangement is also a necessary but insufficient condition for the possibility of a gradual shift to centripetal power sharing ones.